Cytotoxic and hemolytic effects of Tritrichomonas foetus on mammalian cells. - Burgess, D E (1990)
Geographically distinct lines of Tritrichomonas foetus were assayed for their ability to cause cytotoxicity in nucleated mammalian cells and lysis of bovine erythrocytes. T. foetus was highly cytotoxic toward a human cervical cell line (HeLa) and early bovine lymphosarcoma (BL-3) but displayed low levels of cytotoxicity against African green monkey kidney (Vero) cells. In addition to variation in the extent of cytotoxicity toward different targets, differences in the levels of cytotoxicity in the same nucleated target occurred with different parasite lines. Whole T. foetus, unfractionated whole-cell extracts, and parasite-conditioned medium (RPMI 1640 without serum) all caused lysis of bovine erythrocytes. Lytic activity in the conditioned medium was substantially reduced by repeated freezing and thawing or heating to 90 degrees C for 30 min. Damage of mammalian target cells by live T. foetus could be reduced by the presence of protease inhibitors; however, such inhibitors did not diminish the lytic effects of conditioned medium. These results suggested that proteolytic enzymes were necessary for the lytic mechanism of the live parasites but were not required once lytic factors were released into the parasite-conditioned medium. They further suggested that the lytic molecules were either proteins or had proteinaceous components.